2006
DOI: 10.1111/j.1467-6427.2006.00339.x
|View full text |Cite
|
Sign up to set email alerts
|

Expressed emotion and Milan systemic intervention: a pilot study on families of people with a diagnosis of schizophrenia

Abstract: This article presents the results of a pilot study carried out on families of people with a diagnosis of schizophrenia (high‐frequency users of psychiatric services) using a standardized version of systemic family intervention based on the Milan Approach (‘Circular Interview’). We used expressed emotion (EE) to compare and assess two homogeneous samples of families, a treatment group (n = 10) and a control group (n = 8). We found that families participating in circular interviews showed a reduction in criticis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 30 publications
0
14
0
1
Order By: Relevance
“…Vaughn and Leff (1976) were among the first to investigate the effect of EE on schizophrenia patients and found that relapse was associated with high EE in caregivers. As this seminal study, a number of researchers have found similar results (e.g., Bertrando et al, 2006;Butzlaff & Hooley, 1998;Leff & Vaughn, 1985;McFarlane, Dixon, Luken, & Lucksted, 2002;Rockland, 2010).…”
Section: Schizophrenia and Family Dynamicsmentioning
confidence: 59%
“…Vaughn and Leff (1976) were among the first to investigate the effect of EE on schizophrenia patients and found that relapse was associated with high EE in caregivers. As this seminal study, a number of researchers have found similar results (e.g., Bertrando et al, 2006;Butzlaff & Hooley, 1998;Leff & Vaughn, 1985;McFarlane, Dixon, Luken, & Lucksted, 2002;Rockland, 2010).…”
Section: Schizophrenia and Family Dynamicsmentioning
confidence: 59%
“…Circular questions aim at exploring a dyadic relationship as it is seen by a third person by inviting the third person to describe the relationship of two others in their presence 42 43. For example, the instructor may ask the nurse: ‘What did the senior physician do when she entered the operating room (OR) and how did the resident physician react to that?’ Thus, circular questions ask trainees to circle back and comment from an outside perspective on an interaction in which they took part.…”
Section: Debriefings In Simulation-based Trainingsmentioning
confidence: 99%
“…The other four models were classified as level I. They were: Structural‐Strategic Family Therapy (Stanton & Todd, ), Milan Systemic Therapy (Bertrando et al., ), Leeds Systemic Family Therapy (Pote, Stratton, Cottrell, Shapiro, & Boston, ), and Family Systems Therapy (Rohrbaugh, Shoham, Spungen, & Steinglass, ).…”
Section: Resultsmentioning
confidence: 99%